2006
DOI: 10.1158/0008-5472.can-05-4012
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Tamoxifen Regulate Endostatin Generation via Matrix Metalloproteinase Activity in Breast CancerIn vivo

Abstract: Matrix metalloproteinases (MMP) are important regulators of tumor progression and angiogenesis. MMPs generate both proangiogenic and antiangiogenic fragments, such as vascular endothelial growth factor and endostatin. The in vivo activation of MMPs and endostatin generation occur mainly in the extracellular environment by interactions of different cell types. Therefore, these processes are necessary to study in the extracellular space in vivo. Sex steroids play a dominant role in breast carcinogenesis, by larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…For example, it has been suggested that the mechanism by which endothelial cell proliferation and tumour angiogenesis is inhibited is via the ability of MMP-7, -9, and -12 to convert plasminogen in to angiostatin (Dong et al, 1997). This concept was further supported by studies that demonstrated the ability of MMP-9 to generate tumstatin (a potent angiogenesis inhibitor) from type IV collagen (Hamano et al, 2003) and the MMPmediated formation of endostatin (Nilsson and Dabrosin, 2006). A beneficial role for MMP-1 has also been observed in atherosclerosis, whereby the active digestion of interstitial fibrillar collagen (types I, II, and III) by this enzyme affected cell differentiation and impaired cell migration (Lemaitre et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that the mechanism by which endothelial cell proliferation and tumour angiogenesis is inhibited is via the ability of MMP-7, -9, and -12 to convert plasminogen in to angiostatin (Dong et al, 1997). This concept was further supported by studies that demonstrated the ability of MMP-9 to generate tumstatin (a potent angiogenesis inhibitor) from type IV collagen (Hamano et al, 2003) and the MMPmediated formation of endostatin (Nilsson and Dabrosin, 2006). A beneficial role for MMP-1 has also been observed in atherosclerosis, whereby the active digestion of interstitial fibrillar collagen (types I, II, and III) by this enzyme affected cell differentiation and impaired cell migration (Lemaitre et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that prolonged tamoxifen treatment up-regulates MMP-9 expression in cultured MCF-7 cells in vitro and in solid MCF-7 tumors in nude mice [20,26]. To further investigate if these previous findings of increased MMP-9 levels by tamoxifen were involved in TGF-β1 regulation, experiments with this treatment were set-up.…”
Section: Inhibiting Extracellular Mmp Activity Restored the Tamoxifenmentioning
confidence: 99%
“…Depending on tissue distribution and expression levels of individual MMPs and endogenous inhibitors of their activity, these enzymes may either promote or inhibit tumor progression. Lately is has been shown that up-regulation of endogenous MMPs decrease angiogenesis in tumors by the release of matrix-associated anti-angiogenic factors such as angiostatin, tumstatin, and endostatin [17][18][19][20][21]. MMPs have been associated with a positive regulation of TGF-β activity and cell responsiveness to TGF-β [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations